Technical Strategy of Bone Graft Augmentation in the Anterior Maxilla - Ribeiro, Jonathan [UNESP]; Pereira, Rodrigo Dos Santos [UNESP]; Marin, Charles; Granato, Rodrigo; Fernandes, Breno Dos Reis [UNESP]; Mulinari-Santos, Gabriel [UNESP]; Mendes, Bruno Coelho [UNESP]; Hochuli, Eduardo [UNESP] (Wolters Kluwer, 2019)
Bone graft augmentation in the anterior maxilla has a high successful rate. However, suture dehiscence and consequent bone graft exposure can compromise and fail this procedure. Therefore, this article presents a new strategy of closure technique to guarantee the bone graft augmentation. The sutures occur in muscular and mucous planes to avoid suture tension, thus decreasing complications of bone graft augmentation in the anterior maxilla.
Keywords: Bone graft; implants; rehabilitation